2010
DOI: 10.4490/algae.2010.25.4.173
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and distribution of some marine diatoms, Family Rhizosoleniaceae, in Korean coastal waters: a genus Rhizosolenia 1

Abstract: The cell shape, diameter, length of pervalvar axis, external process, segment and areolation characters of the species were examined. All four species were cylindrically shaped, but the external processes differed. Segment striations were regularly straight, and velum showed hexagonal, circular pore and narrow slit. Rhizosolenia formosa and R. hyalina were only occurred in September 2008 from the Yellow Sea, R. bergonii was appeared throughout the year from Korea Strait and Yangyang coasts, and R. setigera was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…As shown in Table 2 of Yun and Lee (2010), Table 2 in Yun et al (2011), and Tables 2-4 in the present study, we divided the 6 genera within the family Rhizosoleniaceae into two groups by morphological diagnostic characteristics including the shape of the external process and girdle segments in the column Lee 2010, Yun et al 2011). The first group had a conoidal valve and loculate areolae and was comprised of Proboscia, Pseudosolenia, Rhizosolenia, Neocalyptrella, and the second group had a flat or rounded valve and poroid areolae and was of Guinardia and Dactyliosolen.…”
Section: Discussionmentioning
confidence: 93%
“…As shown in Table 2 of Yun and Lee (2010), Table 2 in Yun et al (2011), and Tables 2-4 in the present study, we divided the 6 genera within the family Rhizosoleniaceae into two groups by morphological diagnostic characteristics including the shape of the external process and girdle segments in the column Lee 2010, Yun et al 2011). The first group had a conoidal valve and loculate areolae and was comprised of Proboscia, Pseudosolenia, Rhizosolenia, Neocalyptrella, and the second group had a flat or rounded valve and poroid areolae and was of Guinardia and Dactyliosolen.…”
Section: Discussionmentioning
confidence: 93%
“…Lee (1990) arranged a check-list of the marine fossil diatoms and Lee et al (1995) made a check-list of 1457 diatom species from 1929 to 1993 in Korea, Lee (1995) made a checklist of 761 diatom species in Korean coastal waters. In the recent time, many authors have collected the planktonic and periphytic diatoms in the marine waters, and a number of species are newly reported with these floristic studies (Lee and Park 2008, Jung et al 2009, Park and Lee 2010, Yun and Lee 2010, Lee and Lee 2011, Lee et al 2012 However, taxonomic or floristic studies of diatoms have not been reported in the three Islands (Baeknyeong, Daecheong, Socheong) in Yellow Sea of Korea, because these area adjoin the Northern Limit Line (NLL). NLL is important area in Korea, the disputed maritime boundary between North Korea and South Korea in the Yellow Sea.…”
Section: Introductionmentioning
confidence: 99%